Infection due to travel-related carbapenemase-producing Enterobacteriaceae, a largely underestimated phenomenon in Belgium. Issue 3 (June 2015) - Jans, B.; D. Huang, T.-D.; Bauraing, C.; Berhin, C.; Bogaerts, P.; Deplano, A.; Denis, O.; Catry, B.; Glupczynski, Y.
Abstract : Background: Carbapenemase-producing Enterobacteriaceae (CPE) are emerging worldwide, representing a major threat for public health. Early CPE detection is crucial in order to prevent infections and the development of reservoirs/outbreaks in hospitals. In 2008, most of the CPE strains reported in Belgium were imported from patients repatriated from abroad. Actually, this is no longer the case. Objectives and methods: A surveillance was set up in Belgian hospitals (2012) in order to explore the epidemiology and determinants of CPE, including the link with international travel/hospitalization. The present article describes travel-related CPE reported in Belgium. Different other potential sources for importation of CPE are discussed. Results: Only 12% of all CPE cases reported in Belgium (2012–2013) were travel related (with/without hospitalization). This is undoubtedly an underestimation (missing travel data: 36%), considering the increasing tourism, the immigration from endemic countries, the growing number of foreign patients using scheduled medical care in Belgium, and the medical repatriations from foreign hospitals. The free movement of persons and services (European Union) contributes to an increase in foreign healthcare workers (HCW) in Belgian hospitals. Residents from nursing homes located at the country borders can be another potential source of dissemination of CPE between countries. Moreover, the high population density in Belgium can increase the risk for CPE-dissemination. Urban areas in Belgium may cumulate these potential risk factors for import/dissemination of CPE. Conclusions: Ideally, travel history data should be obtained from hospital hygiene teams, not from the microbiological laboratory. Patients who received medical care abroad (whatever the country) should be screened for CPE at admission.